Trade Policy, Economic Interests, and Party Politics in a Developing Country: The Political Economy of CAFTA‐DR1. Issue 1 (1st February 2013) - Hicks, Raymond; Milner, Helen V.; Tingley, Dustin
<x xml:space="preserve">Abstract</x> Developing countries have increasingly opened their economies to trade. Research about trade policy in developed countries focuses on a bottom‐up process by identifying economic preferences of domestic groups. We know less about developing countries. We analyze how economic and political variables influenced Costa Rican voters in a referendum on CAFTA‐DR, an international trade agreement. We find little support for Stolper–Samuelson models of economic preferences, but more support for specific factor models. We also isolate the effects of political parties on the referendum, controlling for many economic factors; we document how at least one party influenced voters and this made the difference for CAFTA‐DR passage. Politics, namely parties using their organizational strength to cue and frame messages for voters, influenced this important trade policy decision. Theories about trade policy need to take into account top‐down political factors along with economic interests.